Abnormal Thyroid Function Laboratory Results Caused by Selective Serotonin Reuptake Inhibitor (SSRI) Antidepressant Treatment - Huijuan Liao; David S. Rosenthal; Salini C. Kumar (Case Reports in Psychiatry)
Mental health issues, especially depressive disorders, are major burdens to the health care systems. This has been more pronounced since the onset of the COVID-19 pandemic. Selective serotonin reuptake inhibitors (SSRIs) are often prescribed for depression. Uncommonly appreciated, however, are the adverse effects these agents may have on thyroid function laboratory test results as well as the clinical thyroidal functional status of such patients, which may lead to erroneous diagnoses and inappropriate treatments. We report on a depressed woman who developed abnormal thyroid biochemical laboratory reports during fluoxetine therapy. After changing to the serotonin and norepinephrine reuptake inhibitor (SNRI) venlafaxine, the thyroid laboratory reports were normalized. In light of this, we wish to alert treating clinicians to this potential significant adverse effect.